Consider the Fibonacci polynomials
$$F_n (x) = \sum_{j = 0}^{\left\lfloor {n/2} \right\rfloor }\binom{n-j}{j} x^{n - 2j} $$ and the Lucas polynomials
$$L_n (x) = \sum_{j = 0}^{\left\lfloor {n/2} \right\rfloor }\frac{n}{n-j }\binom{n-j}{j} x^{n - 2j} .$$

Let $X$ be the multiplication operator $Xp(x)=xp(x)$ on the polynomials, $D_q$ the $q$-differentiation operator defined by $$D_q p(x)=\frac{p(qx)-p(x)}{qx-x}$$ and $A=X+(q-1)D_q$.

Applying the operator $F_n(A)$ to the constant polynomial $1$ has the curious effect that all binomial coefficients $\binom{n}{j}$ are changed to $q$-binomial coefficients ${n\brack j}$ together with some $q$-power. More specifically, we get $$F_n(A)1=F_n(x|q)= \sum_{j = 0}^{\left\lfloor {n/2} \right\rfloor } {q^{j+1\choose 2}}{n-j\brack j} x^{n - 2j} $$ and $$ L_n(A)1=L_n(x|q)= \sum_{j = 0}^{\left\lfloor {n/2} \right\rfloor } {q^{j\choose 2}}{\frac{[n]}{[n-j]}}{n-j\brack j} x^{n - 2j} .$$

Is this an isolated phenomenon or do there exist similar formulae for polynomials? In other words, are there polynomials $p_n(x)$ in one variable $x$ and operators $B(q)$ satisfying $B(1)=X$ such that $p_n(B(q))1$ is a simple or beautiful $q$-analogue of $p_n(x)$?

A trivial example would be $p_n(x)=x^n$ and $B(q)=\epsilon(q)X$ with $\epsilon(q)p(x)=p(qx)$.


Recently I noticed that the Rogers-Szegö polynomials $$R_n(x,s)= \sum_{j = 0}^{n }{n\brack j} x^{j}s^{n-j} $$ can also be represented in this way: $$R_n(x,s)=(x+s+(q-1)xsD_q)^n1.$$ Since this is the most natural $q-$ analogue of the binomial theorem I would be astonished if nobody has as yet seen this fact. The proof is the same as that for the well-known recursion $R_{n+1}(x,s)=xR_{n}(x,s)+(q^n-1)xs R_{n-1}(x,s).$

It follows immediately from the recurrence of the $q-$ binomial coefficients:

$(x+s+(q-1)xsD_q) \sum_{j = 0}^{n }{n\brack j} x^{j}s^{n-j}$ $=\sum_{j = 0}^{n }{n\brack j} x^{j+1}s^{n-j}$ $+\sum_{j = 0}^{n }{n\brack {j}} x^{j}s^{n-j+1}$ $+\sum_{j = 0}^{n }(q^{j}-1){n\brack j} x^{j}s^{n-j+1}$ $= \sum_{j = 0}^{n+1 }({n\brack j}+{n\brack {j-1}}+(q^{j}-1) {n\brack {j}}) x^{j} s^{n-j+1}$ $=\sum_{j = 0}^{n +1}{{n+1}\brack j} x^{j}s^{n-j+1}.$

  • 8
    $\begingroup$ A $q$-rious $q$-estion! I love it. Do you have a reference for your "quantisation" of the Fibonacci and Lucas polynomials? This should not be isolated examples: one could try next the binomial expansion and, if it works, the hypergeometric series. $\endgroup$ – Wadim Zudilin Jul 21 '10 at 10:37
  • 2
    $\begingroup$ Wadim: See e.g. A new class of q-Fibonacci polynomials in Electr.J. Comb. 10(2003),R19 $\endgroup$ – Johann Cigler Jul 21 '10 at 10:56
  • 1
    $\begingroup$ Thanks, Johann! By the way, it's not mentioned that $[n]=(1-q^n)/(1-q)$ and ${m\brack n}=[1][2]\dots[m]/([1]\dots[n]\cdot[1]\dots[m-n])$. $\endgroup$ – Wadim Zudilin Jul 21 '10 at 11:11
  • 1
    $\begingroup$ Re your edit, isn't $1+(q-1)xD_q$ just the $\epsilon(q)$ operator you had earlier ? So $R_n$ arises from the (q-binomial) expansion $(x+s\epsilon)^n$. $\endgroup$ – dke Apr 11 '11 at 17:30
  • $\begingroup$ @dke: yes you are right. $\endgroup$ – Johann Cigler Apr 11 '11 at 19:25

This is not a definitive answer, since it doesn't contain any more examples, but more of an observation.
If you have a sequence $P_n(x)$ for polynomials defined recursively by the formula $$P_n(x)=x^{a_1}P_{n-1}(x)+x^{a_2}P_{n-2}(x)+\cdots+x^{a_k}P_{n-k}(x),$$ and an operator $B(q)$ with $\lim_{q \to 1} B(q)=X$, we get: $$P_n(B)1=B^{a_1}P_{n-1}(B)1+B^{a_2}P_{n-2}(B)1+\cdots+B^{a_k}P_{n-k}(B)1.$$

Denoting $P_n(B)1$ as $\hat P_n(x)$ and supposing that $B$ is linear (which it is, if it depends only on $X$ and $D_q$, like all your examples suggest), we get: $$\lim_{q\to 1}\hat P_n(x)=\lim_{q\to 1}x^{a_1}\hat P_{n-1}(x)+x^{a_2}\hat P_{n-2}(x)+\cdots+x^{a_k}\hat P_{n-k}(x),$$

Thus, $\lim_{q\to 1}\hat P_n(x)$ satisfies the same recursion as $P_n(x)$ does and if the first $k$ terms are equal, then $\lim_{q\to 1}\hat P_n(x) = P_n(x)$ for all $n$. This is precisely the definition of a $q$-analog. Whether it will be interesting is another matter, but I think this must be decided case-by-case.

I noticed that all of your examples have the form $B(q)=X+a(q-1)D_q$. This looks somewhat like a linear term of a series in $D_q$ of the form $$B(q)=X+a_1(q-1)D_q+a_2(q-1)^2D_q^2+\cdots,$$ so maybe if you could find examples with $B$ not linear in $D_q$, it would be very interesting.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.